An in vitro evaluation of the effects of a Yucca schidigera extract and chestnut tannins on composition and metabolic profiles of canine and feline faecal microbiota. Issue 5 (3rd September 2017) - Pinna, Carlo; Vecchiato, Carla Giuditta; Cardenia, Vladimiro; Rodriguez-Estrada, Maria Teresa; Stefanelli, Claudio; Grandi, Monica; Gatta, Pier Paolo; Biagi, Giacomo
ABSTRACT: The in vitro effect of a Yucca schidigera extract (YSE) and tannins from chestnut wood on composition and metabolic activity of canine and feline faecal microbiota was evaluated. Four treatments were carried out: control diet, chestnut tannins (CT), YSE and CT + YSE. The YSE was added to canine and feline faecal cultures at 0.1 g/l, while CT were added at 0.3 g/l for a 24-h incubation. A total of 130 volatile compounds were detected by means of headspace-solid phase microextraction gas-chromatography/mass spectrometry analyses. Several changes in the metabolite profiles of fermentation fluids were found, including a decrease of alcohols (−19%) and esters (−42%) in feline and canine inoculum, respectively, which was due to the antibacterial properties of tannins. In canine inoculum, after 6 h, YSE + CT caused lower cadaverine concentrations (−37%), while ammonia (−4%) and quinolone (−27%) were reduced by addition of CT. After 24 h, the presence of CT resulted in a decrease of sulphur compounds, such as dimethyl sulphide (−69%) and dimethyl disulphide (−20%). In feline faecal cultures, after 6 h, CT lowered the amount of indole (−48%), whereas YSE tended to decrease trimethylamine levels (−16%). Both in canine and feline inoculum, addition of CT and, to a minor extent, YSE affected volatile fatty acids patterns. In canine faecal cultures, CT exerted a marginal inhibitory effect on Escherichia coli population (−0.45 log 10 numbers of DNA copies/ml), while enterococci were increased (+2.06 log 10 numbers of DNA copies/ml) by YSE. The results from the present study show that YSE and tannins from chestnut wood exert different effects on the composition and metabolism of canine and feline faecal microbiota. In particular, the supplementation of YSE and tannins to diets for dogs and cats may be beneficial due to the reduction of the presence of some potentially toxic volatile metabolites in the animals' intestine.